2021
DOI: 10.1111/jerd.12787
|View full text |Cite
|
Sign up to set email alerts
|

Digital scanning under rubber dam: An innovative method for making definitive impressions in fixed prosthodontics

Abstract: Objective To provide a comprehensive protocol for final impressions making under rubber dam isolation by using an intraoral scanner. Clinical consideration Impression making after tooth preparation with rubber dam isolation are impossible with conventional physical impressions, which are not with intraoral scanners. Digital technologies have disrupted dentistry in the last decades, bringing new, straightforward, and more time‐efficient protocols for dental practice. Conclusions Taking in consideration the bene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 25 publications
0
0
0
Order By: Relevance
“…Studies indicate that deep margins, the presence of saliva, or bleeding can compromise the accuracy of images during the scanning process [17]. Therefore, in the quest to improve the efficiency of digital scanning [18,19], it is reported that the use of a rubber dam during the procedure provides a clean and dry environment and also promotes tissue retraction for better image capture. Supporting these approaches, in the described protocol, it was possible to observe the advantages of using isolation, and furthermore, it demonstrated how the performed technique can allow the clinician to quickly and definitively scan during the various stages of the procedure.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies indicate that deep margins, the presence of saliva, or bleeding can compromise the accuracy of images during the scanning process [17]. Therefore, in the quest to improve the efficiency of digital scanning [18,19], it is reported that the use of a rubber dam during the procedure provides a clean and dry environment and also promotes tissue retraction for better image capture. Supporting these approaches, in the described protocol, it was possible to observe the advantages of using isolation, and furthermore, it demonstrated how the performed technique can allow the clinician to quickly and definitively scan during the various stages of the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Rubber dam isolation offers several benefits for both the patient and the clinician [12,13]. The rubber dam can enhance the visual field for the clinician as it eliminates the necessity to constantly reposition the cheek, lips, and tongue, thus facilitating work in the targeted area.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations